2016
DOI: 10.1111/tgis.12233
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsensing smart ambient environments and services

Abstract: Whether it be Smart Cities, Ambient Intelligence, or the Internet of Things, current visions for future urban spaces share a common core, namely the increasing role of distributed sensor networks and the ondemand integration of their data to power real-time services and analytics. Some of the greatest hurdles to implementing these visions include security risks, user privacy, scalability, the integration of heterogeneous data, and financial cost. In this work, we propose a crowdsensing mobile-device platform t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A number of recent projects have explored the sensors on mobile devices from a user-generated data perspective to generate a range of interesting datasets and services as well as research findings [ 21 – 24 ]. Our previous work [ 25 ] has shown that sensors accessible on most current smart-phones can be employed to differentiate place types and could be used in contribution to volunteered geographic services [ 26 ]. Microsoft’s Nericell project aimed at analyzing road and traffic conditions based on data collected via accelerometer and microphone sensors on mobile devices [ 27 ] while [ 28 ] measured urban noise through mobile devices’ sensors.…”
Section: Related Workmentioning
confidence: 99%
“…A number of recent projects have explored the sensors on mobile devices from a user-generated data perspective to generate a range of interesting datasets and services as well as research findings [ 21 – 24 ]. Our previous work [ 25 ] has shown that sensors accessible on most current smart-phones can be employed to differentiate place types and could be used in contribution to volunteered geographic services [ 26 ]. Microsoft’s Nericell project aimed at analyzing road and traffic conditions based on data collected via accelerometer and microphone sensors on mobile devices [ 27 ] while [ 28 ] measured urban noise through mobile devices’ sensors.…”
Section: Related Workmentioning
confidence: 99%
“…The number of platforms encouraging people to share their location has grown significantly over the past decade and so too has the body of literature pertaining to this topic. Much of this work discusses privacy concerns through the lenses of passive (Pagani & Malacarne, 2017; Regalia, McKenzie, Gao, &, Janowicz, 2016) or active (Kummer, Ryschka, & Bick, 2018; McKenzie, Janowicz, & Seidl, 2016) location data collection. A considerable literature investigates the reasons why people choose to share their personal location information (Lindqvist, Cranshaw, Wiese, Hong, &, Zimmerman, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The sheer amount of data collected via these devices, as well as the heterogeneity of the actual content, make these data particularly well suited to the analysis through novel techniques situated in GeoAI (Martin et al 2018). Social sensing and semantic signatures have contributed to fields such as public health (Chaix 2018), activity prediction (Regalia et al 2016), and privacy preservation (Khan et al 2019), to name a few.…”
Section: Social Sensingmentioning
confidence: 99%